Application of Islamic Jurisprudence Methodologies Informulating Parameters Related To The Production of Viral Videos as an Online Sales Marketing Strategy - Mohd Sobri Ellias; Muhammad Adib Samsudin; Salmy Edawati Yaacob (Usuli Faqih Research Centre PLT, 2024)
Al-Qanatir: International Journal of Islamic Studies Vol. 31. No. 2 ( page: 9-19)